TO EVALUATE IVF OUTCOME BETWEEN FLARE-UP VERSUS ANTAGONIST AMONG POOR RESPONDERS’ PROGNOSIS PATIENTS AND RELATED FACTORS AT NATIONAL CENTER FOR ASSISTED REPRODUCTIVE TECHNOLOGY (Vietnam Journal of Community Medicine, 2021)
Objectives: To assess the outcome of Flare-up versus Antagonist protocol and to determine factors related to poor responders.Methodology: this is a random control trial among 834 patients who were predicted to ovarian poor response from 2014 to 2018.Results: The rate of biochemical pregnancy was 4.5% with Flare-up versus 8,1% with Antagonist (p
Keywords: Ovarian poor response, Flare-up, Antagonist, related factors